Learning in project based organizations: processes, mechanisms and main challenges - Daniela Emiliano de Souza; Marly M. Carvalho (Production)
Abstract Paper aims Identify the mechanisms, processes, challenges and other contexts of project-based organizations that affect or are affected by knowledge management. Originality The literature lacks studies that assist project-based organizations in the successful use of knowledge management. We bring these analyzes to this article. Research method We performed a multiple case study applied to two Brazilian companies. Main findings The organizations face challenges due to managerial, operational, and strategic issues. The knowledge management occurs through codification and sharing of data, and both formal and informal events were identified. Implications for theory and practice This paper provides new guidelines for future research, also, several components that affect knowledge management were identified, so professionals will be able to design and implement models with a greater chance of success.